Flow Mahasiswa dalam Pembelajaran Daring Menggunakan Metode Belajar Group Investigation - Prasetyo Adi Nugroho; Dewi Rosiana; Stephani Raihana Hamdan (Sukma: Jurnal Pendidikan)
Online learning during the Covid-19 pandemic is an alternative solution to keep the learning process running, including in universities. This study aims to find out what learning methods with group investigation (GI) methods are, which can improve the quality of the online learning experience and generate flow. This study uses a quantitative approach with an experimental design, namely between participant posttest only control group design. This study compares the effect of using two variants of the Group Investigation method on the flow experience felt by students when learning online. Participants in this study amounted to 27 people (96.3% women). The mean age of the participants was 21.4 years with a standard deviation of 1.12. The results showed that the use of two variants of the Group Investigation method gave the effect of flow with values that tended to be the same. The implication is that the two variants of the Group Investigation method can be used in online learning because they significantly produce student flow experiences in online learning.